Emotional affect in heart transplant candidates: a multicenter longitudinal study - Pennington, Kelly M.; Ahmed, Abdelrahman; Johnson, Bradley K.; Yip, Daniel S.; Benzo, Roberto P.; Schneekloth, Terry D.; Boilson, Barry A.; Daly, Richard C.; Kennedy, Cassie C. (Frontiers in Psychology, 2025)
BackgroundEmotional Affect reflects an individual’s emotional state and can be categorized as positive (PA) or negative (NA). We aimed to characterize affect in heart transplant candidates and evaluate its relationship with pre- and post-transplant psychological and clinical outcomes.MethodsUsing the Positive and Negative Affect Schedule (PANAS), we surveyed adult heart transplant candidates across three transplant centers at baseline (waitlist enrollment), annually on the waitlist, and post-transplant. We assessed PA, NA, and the positivity ratio (PR; PA/NA) as potential predictors of waitlist mortality, post-transplant hospital length of stay, readmissions, and quality of life.ResultsAmong 194 participants, the majority were male (68.6%) and Caucasian (84.3%). Baseline PA (36.0 ± 7.8) and NA (17.9 ± 6.4) were comparable to population norms and remained stable over time. PR was low at baseline (2.3 ± 1.0) and decreased post-transplant (−0.3 ± 1.2; p = 0.03). PA decreased and NA increased post-transplant, but neither change was statistically significant. Affect was not associated with waitlist mortality, delisting, length of stay, or readmissions, but baseline PANAS scores correlated with multiple domains of post-transplant quality of life.ConclusionHeart transplant candidates exhibit a suboptimal PR, which declines post-transplant, highlighting significant psychological stress. Pre-transplant PANAS scores correlated with post-transplant quality of life, suggesting a potential role for psychological screening and intervention in transplant care.